Optimal design and synthesis of rice supply chain - Lim, Jeng Shiun (2013)
Continuous rise in energy cost and increased competitiveness have motivated rice enterprises to find new ways to improve productivity, reduce resource consumption, minimise waste generation, and ultimately, raise profitability. Consequently, there has been extensive research and development works in the conversion of the by-products from rice mills into value-added products. However, most of the works on the improvement of the rice mill and its downstream processes have been carried out in the piece-meal manner. There is a clear need for a systematic framework to optimise and improve the existing rice mill and its value-added processes in an integrated, resource-efficient way. The new framework developed in this thesis includes four key components as described below. Component 1: A new cost-screening framework that is known as the resource-efficient screening (RES) method to screen the rice value chain and select the products and technologies targeted to maximise profit. Component 2: The framework for an integrated, resource-efficient (IRE) rice mill complex to synthesise the processes by evaluating the trade-off between the product revenue, capital investment and utility consumption. The model also considers the seasonality and degradation of rice resources with time. Component 3: A new framework called the integrated, resource-efficient (MSIRE) framework has also been developed for the rice enterprise that operates a cluster of rice mills at different locations. The MSIRE framework is used to determine the product portfolio for each rice mill, the location of the cogeneration system and its optimal scale, whether to expand the current processing facility or to build a new facility and the configuration of the paddy and rice husk logistic network. Component 4: A framework that combines the optimal logistic network of rice husk, with the rice mill’s utility supply network has also been developed. These frameworks were successfully implemented on several case studies involving different scenarios of a national rice enterprise, and produced significant improvement in the enterprise’s profitability.